2018
DOI: 10.1002/hed.25178
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of occult nodal disease in cT1N0 oral cavity squamous cell carcinoma: Review of 2623 cases

Abstract: Sex and tumor differentiation significantly predict occult nodal disease. END is recommended for all moderately and poorly differentiated cT1N0 oral cavity SCC, regardless of the depth of invasion. One can consider not performing END in well-differentiated tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Despite the high incidence of OSCC in young women, gender is not a significant prognostic factor in this study. However, previous studies have suggested that gender can significantly predict occult nodal, and women are more likely to have occult nodal diseases 22…”
Section: Discussionmentioning
confidence: 93%
“…Despite the high incidence of OSCC in young women, gender is not a significant prognostic factor in this study. However, previous studies have suggested that gender can significantly predict occult nodal, and women are more likely to have occult nodal diseases 22…”
Section: Discussionmentioning
confidence: 93%
“…The oral cavity primary site codes included C02.2, C02.3, C03.0, C03.1, C03.9, C04.0, C04.1, C04.8, C04.9, C05.0, C06.0, C06.1, and C06.2. 12 The oropharynx primary site codes included C01.9, C02.4, C05.1, C05.2, C09.0, C09.1, C09.8, C09.9, C10.2, C10.3, and C10.9. 13 The hypopharynx primary site codes included C12.9, C13.0, C13.1, C13.2, C13.8, and C13.9.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…A recent study suggested that END may be unnecessary for well-differentiated T1-stage tumours, 22 but in SEND the DFS HR for this subgroup was 0.54 (95% CI 0.13–2.16). We also conducted analyses (not pre-specified) according to the AJCC 8th edition, 23 because it uses depth of invasion and tumour size.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, evidence from our randomised study that END also benefits pT1-stage tumours that are well-differentiated, contrasts with the conclusion of a recent retrospective study. 22…”
Section: Discussionmentioning
confidence: 99%